Modern Trends in Chinese Language: Integration of Letter Words into the Language System - A.R. Alikberova; T.A. Uryvskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
Various linguistic borrowings have been actively penetrating into the Chinese language since the beginning of the Internet era and active international cooperation. These borrowings (words and abbreviations out of letters from the Western languages, mostly Latin and Greek) have been earlier uncommon for the language. The aim of the present study is to reveal the features of such letter words as of new lexical units in the Chinese language. The main vectors of development of today’s Chinese language have been determined. The sources of letter words and reasons for their distribution in the Chinese language have been considered. On the whole, 239 letter lexemes from the Xiandai Hanyu Dictionary (现代 汉语 词典) have been analyzed. It has been concluded that the rapid spread of letter words may in the long term lead to romanization of the Chinese writing system, as well as to loss of the social and cultural specifics of the Chinese language.